Behavior dynamics faultline in auditing educator: role conflict, proactive personality, and group switching in standards acceptance - Pribadi, Angelia; Arifa, Choirunnisa; Suyanto, Suyanto (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study investigates auditing educators’ (AE) behavior in switching to accounting standard acceptance's fault lines and achieving task performance due to role conflicts and proactive personalities. Design/Methodology/Approach: This research used a 2X2 matrix to categorize role conflict (high vs. low) and proactive personality (transform vs. confront). Then, the data were processed using the ANOVA difference test.Research findings: This study uncovered that AEs with high-role conflict and confront-proactive personalities intend to switch to another group. This research firstly intersects the constructive factors of the role conflict’s level and proactive personalities to explain the AEs’ switching intentions and performance achievement behavior. It also indicates that role conflict could affect AEs’ switching intentions and whether proactive personalities occupy the group memberships. Secondly, this study considers whether the broaden-and-build theory can explain the combination of (high-low) role conflict and (confront-transform) proactive characters. Finally, it describes different AE behaviors when switching intention and achieving the desired task performance. Thirdly, the authors revealed the AEs’ behavior in setting an accounting standard acceptance fault line, an open group that AEs choose due to personal goals. Theoretical Contribution/Originality: This research contributes to the two conceptual contents of role conflict and proactive personalities and accounts for the broaden-and-build theory. Therefore, the fault lines’ members would maintain their membership in a group with positive emotions.Practitioner/Policy Implications: This research implies that group development should include shared emotional values as an antecedent factor for group cohesiveness.Research limitation: The limitation of this study is that the members of the matrix design fault lines did not consider regulations to limit their behavior.